TELOMERES AND TELOMERASE ACTIVITY IN CHRONIC MYELOID LEUKEMIA (REVIEW) - A. S. Lyamkina; T. I. Pospelova (Сибирский научный медицинский журнал, 2019)
A review of literature data on the change in telomere length and telomerase activity at various stages of chronic myeloid leukemia (CML) has been performed. It has been shown that telomere length is reduced faster in the BCR-ABL-positive cells due to their rapid division. It has been reported that telomere length correlates with the remaining time until the disease progresses. Thus, the accelerated reduction of telomeres can be regarded as a sign of a poor prognosis of the disease. It was found that the rate of contraction of telomere length during the progression of the disease was 10–20 times higher than that observed in normal granulocytes and blast cells (tumor samples underwent at least 30–60 additional divisions from the base length of Ph-telomeres). More than 50 % of patients with CML (blast crisis) had a 50-fold increase in telomerase activity. The length of telomeres gradually increased when the cytogenetic response was achieved in the treatment of CML by imatinib or interferon-alpha. Inhibition of telomerase is a new possible therapeutic approach to the treatment of myeloproliferative and solid tumors. Various therapeutic approaches to the inhibition of telomerase have been developed.